The Shelleyan Stylistics - Muh Arif Rokhman (Humaniora, 1996)
Style in literature has been the most unique way of expressing the authors' ideas. It is one of the authors' identities, one that distinguishes a given author from another. Style plays a distinctive role in the language of literature. It is "another way of saying" things. This is to say that both "what is said" and "how it is said - "which are studied under stylistics- exist in any work of literature, that both are not to be taken for granted, and that the vay ot saying it" is often more important than the thing said. Consisting of twenty two lines and written by Percy Bysshe Shetley, "Music" was chosen as tne topic of the study. The focus of the study will be on the relation between the meanings of the poem and its style. The study Isaimed at seeing the uniqueness of the poem's style.